Examining the attributes of electronic waste recycling service: a choice modelling approach - Haron, Nazatul Faizah; Ahmad Sidique, Shaufique Fahmi; Radam, Alias (Canadian Center of Science and Education, 2017)
This paper estimates the economic valuation, discusses preferences for electronic waste (e-waste) recycling, and identifies the most preferred attributes in e-waste recycling. Stratified random sampling from the households in Putrajaya, Malaysia was utilised to obtain the primary data. It provides the readers with an intrinsic satisfaction when choosing a modelling analysis on the valuation of non-market goods using conditional logit simple model. The findings indicate that the option attributes were highly significant and there was no inherent bias towards either the change or no-change option held by the respondents.